Perancangan dan Realisasi Pengatur Kadar Garam pada Aquarium Air Laut Berbasis Mikrokontroler ATMEGA16 - Paryanta Paryanta; Widyo Ari Utomo; Deta Wahyu Herlambang (Sekolah Tinggi Manajemen Informatika dan Komputer AUB - Indonesia, 2019)
Aquarium sea water is a place to keep the fish that live in sea water. Setting levels of salt in the water is one of the problems that often occur. The intensity of the impact on the salt content of appetite that can lead to stress fish so that the fish will die. This thesis will be made the design and realization of the regulator saline seawater aquarium. The main characteristics of the sensor voltage values salinity is issued is inversely proportional to the value of the water levels are detected. If the salt content the higher the voltage value becomes lower. The sensors used in the form of parallel metal pieces which serves as a detector of the change in resistance. The output of the censor will be the input to the ADC. While calculations using ATmega16 microcontroller and the result is displayed on the LCD. If the value of the salt content of sea water aquarium turned microcontroller ATmega16 control valves salt water and fresh water faucet to stabilize the salinity at a certain value. With this thesis is realized, it is expected to reduce the problems in the maintenance of saltwater fish.